Most Popular Theories in Information Systems Research - Ramírez-Correa, Patricio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2016)
The objective of this work is to identify the theories most widely applied in information systems research. In order to achieve this purpose, an exploration of literature 2015 is realized, based on cocitation analysis. Results indicate that Dynamic Capabilities Theory appears as main in the discussion of information systems research.